Diagnosis of urban drainage system in a sub-basin of the stream Osório, Maringá -PR - Gonçalves, Anderson Matheus Bernardino; Roveri, Silas Daniel; Orioli, Monigleicia Alcalde; Jabur, Andréa Sartori; Okawa, Cristhiane Michiko Passos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The surfaces sealing that happen with the growth of cities causes an increase in the volume and speed of runoff. Urban drainage systems are then constructed for conducting the rainwater, as appropriate, to the downstream. In Maringa, Parana, frequent flooding in considered critical points has become a problem of the city management. One of these critical points is the intersection of Palmares Avenue and Guaiapó Avenue, where it has been seen flooding with damage to the population, including loss of material goods. In this context, the aim of this study is to analyse the urban drainage system in a sub-basin of the Osorio Stream that contributes directly at the critical point mentioned above, through simulation scenarios using a computer program. After calibration and validation of the model, three scenarios were simulated with changes in two variables: return time and rain time duration. In all scenarios, it was observed that the drainage systemis undersized and operating in critical conditions, even of low intensity and short duration rains. The conclusion is that there should to be studied low-impact intervention to encourage the infiltration of rainwater into the soil, so that the speed and flow decreases.